2013
DOI: 10.12692/ijb/3.12.232-244
|View full text |Cite
|
Sign up to set email alerts
|

The economic yield evaluation and some of the morphological traits of chickpea cultivars under the influence of different densities

Abstract: In order to study yield and yield components of three chickpea genotypes at different plant densities under dry land conditions, a Field experiment was conducted during 2013 at the Research Farm of the Islamic Azad University of Kermanshah. The experimental design was factorial based on randomized complete block design with three replications. Five plant density (10, 20, 30, 40 and 50 plant/m 2 ) and three chickpea cultivars (ILC482, Arman and Flip84-48C) were factors which studied. Results showed that effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This was 62% higher than that of 50x30cm spacing. Thus, increased plant density enables chickpeas to produce more biomass (Vaghar et al 2013). However, the findings contradicted with the findings of Gezahegn et al (2016), who reported that plant spacing increased biomass in Vicia faba and P. vulgaris respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This was 62% higher than that of 50x30cm spacing. Thus, increased plant density enables chickpeas to produce more biomass (Vaghar et al 2013). However, the findings contradicted with the findings of Gezahegn et al (2016), who reported that plant spacing increased biomass in Vicia faba and P. vulgaris respectively.…”
Section: Discussionmentioning
confidence: 99%